A Research on Online Education Behavior and Strategy in University - Deng, Quan (Frontiers in Psychology, 2022)
After the reform and opening up through a series of rapid development in the world, online education both socially and economically. This area became the representative of the fast-growing economy. However, the Guangfu culture as a crucial component of Cantonese traditional culture is gradually becoming less influential today. It is the college’s responsibility and duty to protect, carry forward and inherit this traditional culture. Especially during this cyber era, whereases the network has become a powerful source for communication and study. There are diversified methods of adaptive learning and a variety of learning behaviors. This article aims to analyze the plausibility of adapting online platforms into the teaching and the needs of students under this teaching mode. A stimulation of applying advanced technology and artificial intelligence into the Guangfu culture’s innovation was also conducted. The contribution shows the users in this platform have a longer study time, compare with those non-platform users, it can mesmerize traditional culture knowledge better than those whose non-users, 21.5% higher in the performance’s test.